The Marxism of Che Guevara: Philosophy, Economics, Revolutionary Warfare - Löwy, Michael (Rowman & Littlefield Publishers, 2007)
In this seminal exploration of Che Guevara's contributions to Marxist thinking, Michael Löwy traces Che's ideas about Marxism both as they related to Latin America and to more general philosophical, political, and economic issues. Now revised and updated, this edition includes a chapter on Guevara's search for a new paradigm of socialism and a substantive essay by Peter McLaren on Che's continued relevance today. Löwy portrays Guevara as a revolutionary humanist who considered all political questions from an internationalist viewpoint. For him, revolutionary movements in Latin America were part of a world process of emancipation. Löwy considers especially Che's views on the contradiction between socialist planning and the law of value in the Cuban economy and his search for an alternative road to the "actually existing socialism" of the Stalinist and post-Stalinist Soviet bloc. Che's varied occupations—doctor and economist, revolutionary and banker, agitator and ambassador, industrial organizer and guerrilla fighter—were expressions of a deep commitment to social change. This book eloquently captures his views on humanity, his contributions to the theory of revolutionary warfare, and his ideas about society's transition to socialism, offering a cohesive, nuanced introduction to the range of Guevara's thought.